Some Observations on Nutrition Cycle and Return of Nutrients in Plantations at New forest - Seth, S. K.; Kaul, O. N.; Gupta, A. C. (Indian Forester, 1963)
It is generally believed that pure plantations are usually exacting on soil nutrients and continued rotations of the same species, on the same site, may deteriorate the site conditions considerably. The annual leaf fall, which in most deciduous species commences by about December, continues for a few months and may even linger on till the rains, brings back some proportion of these nutrients to the soil, but the exact quantities so involved are not known for Indian species. The matter needs all the more attention in view of large scale afforestation of degraded areas in the country with fast growing short rotation species. A preliminary investigation in this regard was therefore considered necessary and data were collected from teak (Tectona grandis), sal (Shorea robusta), chir (Pinus roxburghii), Araucaria cunninghamii and bamboo (Dendrocalamus strictus) plantations at the F.R.I., during the period November, 1960 to June, 1961.